Analysis of Rice Marketing and its Impact on Welfare and Education of Rice Paddy Farmer Family's in Kutai Kartanegara Regency - Karno Karno; Nike Widuri; Gisky Andria Putra; Kezia Arum Sary (Jurnal Penelitian Pendidikan IPA, 2025)
The competitiveness of the local rice market affects the efficiency of the supply chain, thus highlighting the need for a robust supply chain system. Farmers, as the main marketing entity, are crucial in meeting domestic demand. This study aims to analyze the marketing margin, marketing channel, farmer share of rice. The sampling method was conducted in 10 sub-districts, namely Kota Bangun, Muara Kaman, Sebulu, Tenggarong Seberang, Muara Kaman, Marangkayu, Anggana, Samboja, Loa Janan, Loa Kulu, and Tengarong. The research method was carried out qualitatively by conducting an in-depth review so that 100 respondents were collected which were then analyzed using qualitative analysis and marketing analysis. The results show that rice marketing margins vary depending on the marketing channel used. The marketing margin of rice in Kutai Kartanegara Regency varies between IDR 5,300 to IDR 8,000 per kg, depending on the marketing channel and location. Farmer Share: Farmers receive about 53.84% of consumers' final price, while marketing agencies take the rest. Marketing Efficiency: The marketing channels used by paddy rice farmers in Kutai Kartanegara Regency are considered efficient because the marketing efficiency value is below 50%.